(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2016)
The systematics of lingulide brachiopods, from the end-Permian mass extinction interval, is here studied and discussed. The material has been collected from upper Permian (Changhsingian) beds of Southern Alps and Lower Triassic beds of several Tethyan localities, where the surviving phase following the peak the end-Permian mass extinction is recorded. The study contributes to fill the gap of knowledge regarding the lingulide systematics during a time lapse crucial for the fate of the Mesozoic and Cenozoic marine organisms. The systematics is based both on inner shell morphology and shell microstructure, which are considered to be the most useful taxonomical characters to study the lingulide phylogeny. The specimens have been referred to species of the new genus Trentingula, which is characterized by a shell with a secondary layer virgose fabric and a primitive disposition of the ventral muscle umbonal scar in the Lingulidae phylogeny. Trentingula n. gen. comprises four species: T. lorigae n. gen. n. sp., type-species, T. borealis (Bittner), T. mazzinensis n. gen. n. sp., and T. prinothi n. gen. n. sp. The type-species is late Griesbachian – Dienerian in age and has a wide geographic distribution in the western Tethys (Southern Alps and Hungary). Trentingula prinothi n. gen. n. sp. occurs in the Upper Permian Bellerophon Formation of the Dolomites; it has a large shell with a short mantle cavity. Trentingula mazzinensis n. gen. n. sp. occurs in the Griesbachian Mazzin Member of Werfen Formation and is characterized by a small sized shell, about half of the type species, which records the “Lilliput effect” related to the aftermath of the end-Permian mass extinction.